Hypoadrenal syndrome in a patient with amyloidosis secondary to familial mediterranean fever. (29th January 2013) - Gharabaghi, Mehrnaz Asadi; Behdadnia, Aram; Gharabaghi, Mehrnoush Asadi; Abtahi, Hamidreza
Abstract : Amyloidosis is a common complication of poorly controlled familial Mediterranean fever (FMF). A variety of organs including kidneys, heart, liver, thyroid and adrenal glands may be clinically affected. However, involvement of adrenal glands leading to significant inefficiency is rarely seen in FMF patients with amyloidosis. The impairment of neuroendocrine immune system in FMF together with proteinuria in renal amyloidosis is a challenge while interpreting adrenal function tests. Here we present a case report of a 42-year-old man with FMF and renal failure due to amyloidosis whose disease course was complicated by adrenal insufficiency.